Pembuatan Peta Desa di Desa Warawatung Kecamatan Nagawutun Kabupaten Lembata - Selestinus Trichinas Gafita Putra; Timoteus Ua; Yosep Riang; Kristianus Simon H. Molan (Jurnal Kemitraan Masyarakat, 2024)
The creation of a village map is a strategic effort in effective village planning and development. Warawatung Village in Nagawutun Subdistrict, Lembata Regency, is one such village that requires a map to support local development planning. The Community Service Program (KKN) conducted by students of Universitas Widya Mandira Kupang aims to produce a comprehensive village map with geospatial information, including boundary limits, infrastructure networks, public facilities, and geographical conditions. The methods used in the creation of this map include site surveys, manual sketching, digital map-making processes, and the handover of the final product to the village authorities. The result of this activity is a map that not only facilitates development planning but also serves as a promotional tool to enhance the village's appeal to tourists and investors. Thus, this village map is expected to become a vital tool for the development of Warawatung Village.